The Role of Enterpeuniral University of the Excellent Performance - Hazha khattab Muhammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research aims to study the Enterpeuniral University of the Excellent Performance of the college of Administration & . The researcher presented the literature on these subjects. The research problem was identified through several questions focused on the nature of the relationship and the influence between the independent variable and the dependent variable. The main and secondary hypotheses and for the verification of these hypotheses were subjected to a series of statistical tests and the approach of research descriptive analytical method. The research sample was determined from the number of members lecturer of the college of Administration Economic – Sallahaddin University, And distribution (90) form the respondents of individuals have been obtained (83) form all of which are valid for analysis, (SPSS) was used to study the assumed relationships in the research model. The research reached a number of conclusions. The results of the correlation analysis revealed the existence of positive and high relations between Enterpeuniral University and Excellent Performance at the macro and micro levels. This confirms that the researched universities benefit from the identification of the Enterpeuniral University to Excellent Performance, the most important of which is the researcher’s suggestion that colleges should retain the knowledge they possess, as well as acquire new knowledge from external sources.